2018
DOI: 10.1002/admi.201701303
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Elasticity and Ultralow Friction of Hydrogenated Fullerene‐Like Carbon Films: Associated with the Size of Graphene Sheets

Abstract: such as high-hardness/strength, excellent elasticity, and high compressibility. [1][2][3][4] Carbon nitride films, [5] pure carbon films, [6] and hydrogenated carbon films [7] containing these fullerene-like structures have been proved to possess excellent elastic recovery rate (85%, 80%, and 85%, respectively) and high hardness values (60, 53, and 19 GPa, respectively). In particular, hydrogenated fullerene-like carbon (FLC:H) films can also exhibit ultralow friction behaviors, which are desirable to minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…37 Our previous work has demonstrated that the high elasticity of a film is beneficial to the superlow friction. 39,40 Figure 4d and Fig. S7 show the mechanical properties of the wear tracks with and without the Pebax-BNNS/water dispersion as a lubricant.…”
Section: Discussionmentioning
confidence: 99%
“…37 Our previous work has demonstrated that the high elasticity of a film is beneficial to the superlow friction. 39,40 Figure 4d and Fig. S7 show the mechanical properties of the wear tracks with and without the Pebax-BNNS/water dispersion as a lubricant.…”
Section: Discussionmentioning
confidence: 99%
“…The exceptional physicochemical properties of the fullerene family and, above all, its main representative, C 60 , predetermine the broad practical interest in the use of these compounds. This is quite understandable: compounds with unique optical [ 2 4 ], electrophysical [ 5 7 ], mechanical [ 8 10 ], tribological [ 11 13 ], sorption [ 14 17 ], and biological properties [ 18 20 ], and even new dyes and catalysts [ 21 25 ], have already been discovered among functionalized fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, lots of experimental studies on the tribological properties of DLC films have been carried out by investigating the effects of intrinsic properties, i.e., hydrogen concentration, hardness, metal/nonmetal doping, and so on [8][9][10][11]. However, the tribological properties of DLC films depend on not only the intrinsic parameters, but also many extrinsic factors, such as sliding velocity, normal load, environment atmosphere, and properties of friction interfaces [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%